294PValidation of the 8th edition of AJCC/UICC staging system for nasopharyngeal carcinoma: Results from a non-endemic cohort with long-term follow-up. (24th November 2019) - Wu, L-R; He, X
Abstract: Background: This study aimed to validate the 8th edition of American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) TNM staging system for nasopharyngeal carcinoma (NPC) in a non-endemic region. Methods: We recruited 614 patients with histology-proven, previously untreated, non-metastatic NPC treated by intensity-modulated radiotherapy (IMRT) at our center. Harrell's concordance index (c-index) and time-dependent receiver operating characteristic (TD-ROC) analysis were applied to compare the prognostic discrimination between the 7th and 8th edition staging system. Results: For T category, the local recurrence-free survival (LRFS) Kaplan-Meier curves of T1, T2 and T3 were well separated in the 8th edition; however, LRFS did not significantly differ between T3 and T4 (P = 0.15). Moreover, the 7th edition achieved higher c-index (0.703 [95% CI, 0.618-0.788] vs. 0.686 [95% CI, 0.604-0.768]) and area under curve ([AUC], 5-year: 0.681 vs. 0.672; 10-year: 0.645 vs. 0.615) than 8th edition for LRFS. With regard to N category, the 8th edition achieved higher c-index (0.800 [95% CI, 0.755-0.847] vs. 0.757 [95% CI, . 0.704-0.811]) and AUC (5-year 0.728 vs. 0.685; 10-year: 0.748 vs. 0.680) for distant metastasis-free survival. In terms of overall stage, the 8th edition also had higher c-index (0.800 [95% CI, 0.755-0.845] vs. 0.724 [95% CI, 0.676-0.773]) and AUC (5-year: 0.730 vs. 0.713; 10-year: 0.734 vs. 0.677) compared with 7th edition for overall survival. Conclusions: The 8th edition of AJCC/UICC TNM staging system achieved significantly better prognostic discrimination than the 7th edition with regard to N category and overall stage but not T category. Legal entity responsible for the study: Department of Radiation Oncology, Jiangsu Cancer Hospital, Nanjing Medical University Affiliated Cancer Hospital, Jiangsu Institute of Cancer Research. Funding: The National Natural Science Foundation of China (No. 81672989; No. 81872192). Disclosure: All authors have declared no conflicts of interest.